2020
DOI: 10.1101/2020.05.15.095794
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phylogenetic Analysis of SARS-CoV-2 Genomes in Turkey

Abstract: COVID-19 has effectively spread worldwide. As of May 2020, Turkey is 3 among the top ten countries with the most cases. A comprehensive genomic 4 characterization of the virus isolates in Turkey is yet to be carried out. Here, we built a 5 phylogenetic tree with 15,277 severe acute respiratory syndrome coronavirus 2 (SARS-6 CoV-2) genomes. We identified the subtypes based on the phylogenetic clustering in 7 comparison with the previously annotated classifications. We performed a phylogenetic 8 analysis of the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Extremely rapid whole genome sequencing has enabled nearly real-time tracing of the evolution of the SARS-CoV-2 pandemic [1][2][3][4][5] . By leveraging sequence data produced by labs throughout the world, researchers can trace transmission of the virus across human populations [6][7][8][9][10][11][12][13][14] . Typically, viral evolution is encapsulated by a phylogenetic tree relating all of the virus samples in a large set to one another [5,[15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…Extremely rapid whole genome sequencing has enabled nearly real-time tracing of the evolution of the SARS-CoV-2 pandemic [1][2][3][4][5] . By leveraging sequence data produced by labs throughout the world, researchers can trace transmission of the virus across human populations [6][7][8][9][10][11][12][13][14] . Typically, viral evolution is encapsulated by a phylogenetic tree relating all of the virus samples in a large set to one another [5,[15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…We have not performed a comprehensive phylogenetic evaluation in this study. Nevertheless, a recent analysis, albeit with a lower number of genomes, suggested multiple independent international virus introductions in Anatolia and inland spread ( Adebalı et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A phylogenetic analysis carried out in Turkey, with the first 30 genomes isolated from SARS-CoV-2 in this region, showed that the introduction of the virus in the country occurred before the first reported case of infection. The study demonstrated that the virus circulated in Turkey from several independent international introductions and revealed a hub for inland transmission [ 139 ].…”
Section: Use Of Bioinformatics and Molecular Modeling As Technologmentioning
confidence: 99%